Study of mechanical and flammability properties of polypropylene/microcrystalline cellulose composites filled with nano-sized aluminium hydroxide (ATH) particles - Samat, Noorasikin; Zulkapli, Nor Najihah; Halim, Zahurin; Ahmad, Zuraida; Abang Ismawi Hassim, Dayang Habibah (Trans Tech Publications, Switzerland, 2015)
The mechanical and flame properties of polypropylene/ microcrystalline cellulose (MCC) composites containing different loading of aluminium hydroxide (ATH) nanoparticles from 3 to 20wt% was studied. Maleic anhydride grafted polypropylene (MAPP) was used as a coupling agent in the composites. The mechanical properties of PP/MCC composites were characterized by tensile and impact tests while the flame properties were evaluated by UL-94 and oxygen index tests. It was shown that the addition of ATH improved the mechanical and flame resistance properties PP/MCC composites, mainly in the composites with MAPP. Fracture surface observations in samples with MAPP show better dispersion and adhesion of fillers (MCC and ATH). Flame retardancy also enhanced along with the ATH loading.